1999
DOI: 10.1021/bi983037t
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Studies of the Folding of Human Lysozyme and the Origin of Amyloidogenic Behavior in Its Disease-Related Variants

Abstract: The unfolding and refolding properties of human lysozyme and two amyloidogenic variants (Ile56Thr and Asp67His) have been studied by stopped-flow fluorescence and hydrogen exchange pulse labeling coupled with mass spectrometry. The unfolding of each protein in 5.4 M guanidine hydrochloride (GuHCl) is well described as a two-state process, but the rates of unfolding of the Ile56Thr variant and the Asp67His variant in 5.4 M GuHCl are ca. 30 and 160 times greater, respectively, than that of the wild type. The ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
150
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 167 publications
(160 citation statements)
references
References 38 publications
8
150
0
2
Order By: Relevance
“…In-depth characterization of two of the disease-associated variants, I56T and D67H, as well as the non-diseaserelated T70N variant, has been performed using a variety of biophysical techniques. [7][8][9][10][11][12][13][14] Deposits of I56T and D67H formed in vitro possess the key characteristics of amyloid fibrils; these include their fibrillar morphology in TEM images, their displays of birefringence upon binding the dye Congo red and a typical cross-β X-ray diffraction pattern. [10][11][12] The kinetics of in vitro fibril formation by both I56T and D67H are sigmoidal, showing a lag phase followed by an exponential growth phase typical of amyloidogenic systems.…”
Section: Introductionmentioning
confidence: 99%
“…In-depth characterization of two of the disease-associated variants, I56T and D67H, as well as the non-diseaserelated T70N variant, has been performed using a variety of biophysical techniques. [7][8][9][10][11][12][13][14] Deposits of I56T and D67H formed in vitro possess the key characteristics of amyloid fibrils; these include their fibrillar morphology in TEM images, their displays of birefringence upon binding the dye Congo red and a typical cross-β X-ray diffraction pattern. [10][11][12] The kinetics of in vitro fibril formation by both I56T and D67H are sigmoidal, showing a lag phase followed by an exponential growth phase typical of amyloidogenic systems.…”
Section: Introductionmentioning
confidence: 99%
“…Besides being, in fact, one of the best characterized enzymes, its fibrillogenic mechanism is not influenced by protein fragmentation; nor, to our knowledge, does the wild-type species generate amyloid deposits in vivo, even in the elderly. Thorough analysis of several biochemical properties of the amyloidogenic variants in comparison to the wildtype species showed that pathogenic lysozymes are less stable than wild-type (3)(4)(5)(6)(7)(8). This thermodynamic destabilization correlates with an increased concentration of partly unfolded intermediates that self-aggregate into fibrillar polymers.…”
mentioning
confidence: 99%
“…The main resultant peptide in the mass spectrum spans from the N-terminus of the protein to an internal part of α-helix 1, the end product of CPY digestion. This indicates that before fibril formation the protein unfolds partially, as has been postulated for other proteins with amyloid propensity [16][17][18]. In fact, we have demonstrated previously that when we changed the pH by dialysis from 7.0 to 3.0 in a diluted sample that was not submitted to high temperature, as is the case in this experiment, the CD spectrum corresponded to an αβ-conformation with an increase in the random-coil conformation (the minimum at 208 nm is increased) [6].…”
Section: Sensibility Of the Wt To Proteolysis During Fibril Formationmentioning
confidence: 53%